Estimation of Groundwater Recharge for the Main Aquifer in the Northeastern Missan Governorate, South of Iraq Using Chloride Mass Balance Technique - Atiaa, Alaa; Al-Shamma'a, Ayser; Aljabbari, Mukdad (Iraqi Journal of Science, 2023)
The groundwater recharge from rainfall for the main shallow aquifer in the northeastern Missan governorate south of Iraq is investigated via classical and refined chloride mass balance techniques. Application of both techniques reveals that the mean annual groundwater recharge is 0.82 mm/y. The annual recharge received by the aquifer approximately reaches to three million cubic meters after multiply this figure by the area of the study area (about 1856 km2). This figure represents a renewable storage from which a sustainable management of the groundwater reserve could be implemented. The techniques applied are robust, costly-effective, and could be used with other methods such as groundwater table fluctuation method to give a more realistic value for this very important parameter.